The nano world of Munir Nahfey - Saquib, Nazmus; Faris, Waleed Fekry (IIUM Press, 2011)
The objective of this chapter is to find out the achievement of Munir Nayfeh in Particle Physics as well as in Nanotechnology. The significance of this chapter proves Nayfeh as one of the pioneers of this field and his contribution has taken the world in to another sphere of Nanotechnology. The methodology has been taken in this chapter are from Internet information, Scientific journals and books.